Coupled Fixed Point Theorems with Rational Type Contractive Condition in a Partially Ordered G-Metric Space - K. Chakrabarti (Journal of Mathematics)
Coupled fixed point theorems for a map satisfying mixed monotone property and a nonlinear, rational type contractive condition are established in a partially ordered G-metric space. The conditions for uniqueness of the coupled fixed point are discussed. We also present results for the existence of coupled coincidence points of two maps.